Design and in vitro evaluation of pH-sensitive crosslinked chitosan-grafted acrylic acid copolymer (CS-co-AA) for targeted drug delivery. Issue 5 (24th March 2022) - Ijaz, Hira; Tulain, Ume Ruqia; Minhas, Muhammad Usman; Mahmood, Asif; Sarfraz, Rai Muhammad; Erum, Alia; Danish, Zeeshan
Abstract: In current research study, novel chitosan-based hydrogel was formulated via crosslinking graft copolymerization of acrylic acid (AA) and chitosan. Potassium persulfate was used as free radical generator in the presence of crosslinker (methylene bis acrylamide (MBA)). FTIR spectroscopy was employed to elucidate structure of hydrogel. Moreover, sample morphology was examined by scanning electron microscopy (SEM) and thermal analysis was conducted by using thermogravimetric analysis (DSC/TGA). The influence of reaction variables such as concentration of chitosan (CS), acrylic acid (AA) and MBA was optimized to attain hydrogel with significant swelling capacity. Chitosan-g-AA hydrogel depicted pH responsive attributes and swelling–deswelling pulsatile behavior was recorded at pHs 1.2 and 7.4. This on–off switching makes hydrogel ideal candidate for controlled drug delivery. Graphical Abstract: UF0001